2012
DOI: 10.1073/pnas.1203396109
|View full text |Cite
|
Sign up to set email alerts
|

Brain anomalies in children exposed prenatally to a common organophosphate pesticide

Abstract: Prenatal exposure to chlorpyrifos (CPF), an organophosphate insecticide, is associated with neurobehavioral deficits in humans and animal models. We investigated associations between CPF exposure and brain morphology using magnetic resonance imaging in 40 children, 5.9-11.2 y, selected from a nonclinical, representative community-based cohort. Twenty high-exposure children (upper tertile of CPF concentrations in umbilical cord blood) were compared with 20 low-exposure children on cortical surface features; all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
268
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(283 citation statements)
references
References 49 publications
12
268
0
3
Order By: Relevance
“…Although postnatal exposures to organophosphate pesticides have also been examined, when taken together, studies have demonstrated more frequent and/or stronger associations between prenatal exposures and adverse outcomes than with postnatal exposures (4,6,9). However, to date, studies examining these associations have focused primarily on cohorts that were likely exposed to higher-than-national-average levels of organophosphate pesticides, either through heavy use of pesticides for inner-city pest control or as members of farming communities (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although postnatal exposures to organophosphate pesticides have also been examined, when taken together, studies have demonstrated more frequent and/or stronger associations between prenatal exposures and adverse outcomes than with postnatal exposures (4,6,9). However, to date, studies examining these associations have focused primarily on cohorts that were likely exposed to higher-than-national-average levels of organophosphate pesticides, either through heavy use of pesticides for inner-city pest control or as members of farming communities (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The purpose of the current study was to examine the association of prenatal exposure to organophosphate pesticides with early childhood cognition in a sample of children whose mothers' exposures during pregnancy are similar to reported US levels. This study was initiated after the ban of residential use of chlorpyrifos in 2001, whereas previously published studies included mostly subjects exposed prior to the residential ban (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Children's exposures to developmental neurotoxicants also occur via both inhalation and dermal exposures to environmental contaminants. Other well-known or suspected developmental neurotoxicants include ethanol, antidepressant or anticonvulsant pharmaceuticals, arsenic, lead, toluene, polychlorinated biphenyls (PCBs), organophosphate or organochlorine pesticides and a variety of industrial chemicals 3,[9][10][11][12][13][14][15] . The number of chemicals known to be developmentally neurotoxic in humans is limited at present.…”
Section: Introductionmentioning
confidence: 99%
“…In his Letter to the Editor (1), Juberg conflates two sequential statements in our paper (2). The references cited in his letter pertain to the sentence preceding the one in question and relate to the "direct neurotoxic effects of early CPF exposure in animals" (ref.…”
mentioning
confidence: 99%